Solar Cell Materials by Design: Hybrid Pyroxene Corner‐Sharing VO4 Tetrahedral Chains. Issue 9 (21st March 2017) - El‐Mellouhi, Fedwa; Akande, Akinlolu; Motta, Carlo; Rashkeev, Sergey N.; Berdiyorov, Golibjon; Madjet, Mohamed El‐Amine; Marzouk, Asma; Bentria, El Tayeb; Sanvito, Stefano; Kais, Sabre; Alharbi, Fahhad H.
Abstract: Hybrid organic–inorganic frameworks provide numerous combinations of materials with a wide range of structural and electronic properties, which enable their use in various applications. In recent years, some of these hybrid materials—especially lead‐based halide perovskites—have been successfully used for the development of highly efficient solar cells. The large variety of possible hybrid materials has inspired the search for other organic–inorganic frameworks that may exhibit enhanced performance over conventional lead halide perovskites. In this study, a new class of low‐dimensional hybrid oxides for photovoltaic applications was developed by using electronic structure calculations in combination with analysis from existing materials databases, with a focus on vanadium oxide pyroxenes (tetrahedron‐based frameworks), mainly due to their high stability and nontoxicity. Pyroxenes were screened with different cations [A] and detailed computational studies of their structural, electronic, optical and transport properties were performed. Low‐dimensional hybrid vanadate pyroxenes [A]VO3 (with molecular cations [A] and corner‐sharing VO4 tetrahedral chains) were found to satisfy all physical requirements needed to develop an efficient solar cell (a band gap of 1.0–1.7 eV, strong light absorption and good electron‐transport properties). Abstract : A chain for the better : A new class of materials for photovoltaic applications has been developed, based on low‐dimensional hybrid vanadate pyroxenes [A]VO3 (with molecular cations [A] and corner‐sharing VO4 tetrahedral chains). These materials were found to satisfy the physical requirements needed to develop an efficient solar cell (a band gap of 1.0–1.7 eV, strong light absorption and good electron‐transport properties).